Central Asia: Crossing the Threshold at Different Speeds - Alimukhamedov, Farkhad (International Higher Education, 2020)
The higher education systems of Central Asian countries have been rapidly impacted by global changes. New international universities and a high rate of student mobility are promising steps of internationalization in this landlocked region. Recent developments show the overall importance of quality, recognition, and scientific cooperation in the region, despite gaps between national internationalization policies.